INTRODUCTION TO “DIRECT INTERACTION: METHODS OF RESEARCH, EPISTEMOLOGY, CONCEPTUALIZATION (I)” – THEMATIC DOSSIER - Ion COPOERU (Studia Universitatis Babeș-Bolyai. Philosophia)
“Are you investigating direct multimodal interactions?” This is the first question that we addressed to our colleagues who are conducting research in fields, such as linguistics, education science, didactics, psychology, sociology, anthropology and, of course, philosophy. If you are interested in knowing more about this topic or you are conducting yourself an investigation in this area, you might enjoy some of the research papers presented at the hybrid event hosted by the Dept. of Philosophy of Babeş-Bolyai University from Cluj-Napoca in June 2nd – 4th, 2022. The interactions constituted a topic of investigation in social sciences and philosophy starting with the beginning of the 20th century. Initially, the study of interactions was associated with the investigation of human experience. Georg Simmel and Erving Goffman have shifted the understanding of social phenomena by reversing their traditional framing as means-end and cause-effect chain models.